Overview of knowledge, attitudes and barriers associated with HPV vaccination in Beirut, Lebanon - Lauren Hourani; Macy Zaatar; Jawad Hoballah; Kamil Kadi; Maria Yasmine; Hussein Hijazi; Natalie Estelly; Jad Mrad; Miran A. Jaffa (Global Public Health)
Background: Human Papillomavirus (HPV), a prevalent sexually transmitted infection carrying significant risks ranging from benign lesions to various types of malignancies, represents a matter of great public health concern. Notably, most Arab countries lack public awareness campaigns or national immunization programs. This study aims at assessing the overall knowledge on HPV and HPV vaccination among the Lebanese population, exploring the prevalent attitude on the matter, and identifying barriers and misconceptions that prevent individuals from receiving the HPV vaccine.Methods: A cross-sectional study was conducted in Beirut, on 201 participants aged between 18 and 36 years old. We performed ordinal analysis to assess the trend between Knowledge levels, attitude levels and hesitancy Levels.Results: Majority of participants (77%) demonstrated a low level of knowledge on HPV vaccination, 50% held a positive attitude, with only 18.4% being already vaccinated. Negative trend was identified between levels of knowledge, attitude and hesitancy (gamma = −0.7415, p-value < 0.01; gamma= −0.58, p-value < 0.01 respectively). Unavailability or limited access to the vaccine, and misconceptions about HPV immunization were shown to be impeding vaccination.Conclusion: Analysis of our results strongly suggests that improving knowledge and attitudes is likely to foster trust and reduce hesitancy, thereby promoting higher vaccine uptake.